Kinship Care dalam Keluarga ‘Imran: Kajian Hermeneutika Wilhelm Dilthey pada Surat Ali ‘Imran Ayat 37 dan 44 - Kafiyah, Fitroh Ni’matul; Komarudin, Edi; Riyani, Irma (Jurnal Penelitian Ilmu Ushuluddin, 2024)
Kinship Care is a form of childcare by close relatives such as grandparents, aunts, uncles, or siblings when biological parents cannot fulfill their parenting responsibilities. In Indonesia, Kinship Care often arises in the context of poverty, migration, parental death, or the inability of parents to care for their children for various reasons, including death, illness, or legal issues. This research is a desk study using Wilhelm Dilthey's hermeneutic analysis method to explore three aspects, namely Erlebnis (experience), Ausdruck (expression), and Verstehen (understanding), in Surah Ali 'Imran verses 37 and 44. The results of this study conclude that in the Kinship Care pattern, Zakariya has four patterns in caring for Maryam, security and support, space for children, financial security, dialogue and appreciation for children. Then, suggestions for further research related to Kinship Care studies to explore broader patterns using different hermeneutical theories and different figures in the Qur'an can also be taken in relevance to different contexts so that they can reach ideal patterns for Kinship Care studies.